Variations in the epidemiology of primary, secondary and early latent syphilis, England and Wales: 1999 to 2008. Issue 3 (24th January 2011) - Jebbari, Heather; Simms, Ian; Conti, Stefano; Marongiu, Andrea; Hughes, Gwenda; Ward, Helen; Powers, Cassandra; Thomas, Daniel Rh; Evans, Barry
Abstract : Objective: To investigate factors associated with variations in diagnoses of primary, secondary and early latent syphilis in England and Wales. Methods: Data were derived from two sources: diagnoses made in genitourinary medicine clinics reported on form KC60, and information collected through National Enhanced Syphilis Surveillance (NESS). Multinomial regression modelling was used for data analysis. Results: Between 1999 and 2008, 12 021 NESS reports were received, 54% of KC60 reports. The dominant profile of the epidemic was one of white men who have sex with men aged 35–44, often co-infected with HIV, centred in larger cities. During this period, the proportion of primary cases increased over time, while the proportion of secondary cases fell. Primary cases exceeded secondary cases by 2004. The proportion of early latent cases remained relatively stable over time and tended to be lower than that of primary and secondary infection. Patients who attended because they had symptoms of infection, had been identified through partner notification, were HIV positive, and were UK born were more likely to present with primary or secondary infection than with early latent infection. A higher proportion of early latent cases were seen among patients who were Asian, had contacted sexual partners through saunas, bars and the internet, had untraceable partners, and had acquired infection in Manchester. Conclusions: The continuing syphilis epidemic indicates that control has only been partially effective, with ongoing transmission being sustained. Intensive and targeted efforts delivered locally are required to interrupt further transmission.